COMPARATIVE STUDY OF SPAN 40 AND SPAN 60 BASED SOY-GELS FOR TOPICAL DRUG DELIVERY - SHUBHAM MUKHERJEE; DIPANJANA ASH; GOPA ROY BISWAS; SUTAPA BISWAS MAJEE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Hydrogels or emulgels are recommended for topical application to elicit a local effect. However, they suffer from stability problems. The present study deals with the formulation and comparison of thermally stable soybean oil-based novel topical organogels (soy-gels) using two different gelators (Span 40 and Span 60) for controlled drug delivery. Methods: Soy-gels (8 batches) were developed with Span 40 and Span 60 by solid fiber mechanism and characterized for viscosity, gelation kinetics behavior, gel-sol transition parameters, drug content, in vitro drug release pattern, and changes occurring during accelerated thermal stability studies. Results: Fourier transformed infrared spectroscopic confirmed the compatibility among the organogel components and paracetamol. The formulations exhibited skin and hemocompatibility. The viscosity of Span 60 based soy-gels was found to be approximately 10 times higher than those of Span 40 based formulations. In comparison to Span 40, Span 60 induced faster gelation (3–6 min) of soybean oil at lower concentration (16% w/v) forming less flexible but thermally more stable soy-gels demonstrating higher Tg values. Higher flexibility and lower viscosity accounted for improved drug diffusion (both Fickian and non-Fickian) from Span 40 gels of varying concentrations in pH 5.8. However, zero-order drug release was observed in organogel with 18% w/v Span 40 only and all Span 60-based formulations except the one with 22% w/v Span 60. Non-Fickian drug diffusion occurred from Span 60 based soy-gels. A gradual increase in gelation time was observed until five cycles of freeze-thaw. Conclusion: Therefore, the choice of organogelator governs the rheological, thermal, and drug diffusion properties of soy-gels intended for topical application.